Making Intelligence Analysis More Intelligent: Using Numeric Probabilities. Issue 3 (15th April 2016) - Barnes, Alan
Abstract: A number of researchers have advocated the use of explicit numeric probabilities in the drafting and presentation of intelligence assessments. A trial of this methodology by a Canadian assessment unit has demonstrated that numeric probabilities can be used effectively in the preparation of intelligence reports. The practice leads analysts to pay greater attention to the estimative judgments they make and allows for greater transparency in understanding the degree of certainty that they attach to their conclusions. The use of numeric probabilities highlights the need for a consistent mapping standard for verbal probability terms. However, implementing the methodology requires overcoming a widely shared aversion among analysts and intelligence managers to thinking in numeric terms.